2017
DOI: 10.26434/chemrxiv.5318188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

10-step Synthesis of 20-nor-Salvinorin A by Dynamic Strategic Bond Analysis

Abstract: Salvinorin A (SalA) is a plant metabolite that agonizes the human kappa-opioid receptor (κ-OR) with high affinity and high selectivity over mu-and delta-opioid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…5,6,7,8 We recently identified angular methyl C20 as a main contributor to scaffold instability due to a 1,3-diaxial interaction with the C12 hydrogen, which is relieved by epimerization. 9 We found that deletion of C20 reversed the stability of the SalA scaffold and caused the potent isomer to predominate (1:2.5). This new lead compound, 20-nor-SalA, retained the high potency and selectivity of SalA itself, and its facile synthesis allowed the generation of new aryl analogs using a carboxylate-directed Heck reaction.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…5,6,7,8 We recently identified angular methyl C20 as a main contributor to scaffold instability due to a 1,3-diaxial interaction with the C12 hydrogen, which is relieved by epimerization. 9 We found that deletion of C20 reversed the stability of the SalA scaffold and caused the potent isomer to predominate (1:2.5). This new lead compound, 20-nor-SalA, retained the high potency and selectivity of SalA itself, and its facile synthesis allowed the generation of new aryl analogs using a carboxylate-directed Heck reaction.…”
mentioning
confidence: 80%
“…This new lead compound, 20-nor-SalA, retained the high potency and selectivity of SalA itself, and its facile synthesis allowed the generation of new aryl analogs using a carboxylate-directed Heck reaction. 9 We hypothesized that further scaffold stabilization might be possible by removing the restriction of the small dihedral angle (0° ideal) 10 enforced by the C-ring lactone. Here we show that O→C replacement (lactone→cyclo-hexanone), combined with C20 deletion, stabilizes the SalA scaffold to the point where no epimerization is observed under conditions that equilibrate SalA.…”
mentioning
confidence: 99%
See 3 more Smart Citations